Ekstrak Daun Bambu Tali (Gigantochloa Apus) Sebagai Green Inhibitor Terhadap Laju Korosi Baja Karbon Dalam Media HCL - Abdullah Agung Hayyuka; Komalasari Komalasari; Rozanna Sri Irianty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Corrosion is a decrease in the quality of a metal due to an electrochemical reaction between the metal and its environment. The use of inhibitors is the right way to protect the internal partsof metal pipes from corrosion. Gigantochloa apus leaves extract can be used as a natural inhibitor. This research aims to characterize the results of Gigantochloa apus leaves extract, determine the rate of corrosion in carbon steel with the addition of inhibitors from Gigantochloa apus leaves extract, and determine the variables that affect the corrosion rate.The extraction method used is soxhletation with an ethanol:distilled water ratio of 1:4. The variables used in the form of 0.5M, 1.0M, 1.5M HCl media variations and immersion time for 24, 32, 40 hours with inhibitors concentration of 2 g/L and weight loss method in carbon steel. The results showed that Gigantochloa apus leaves extract contained tannin compounds (phenolic OH groups), namely in waves 3234.76 and 3350.50 cm-1 as much 17.54 mg/g. The best corrosion rate inhibitors on carbon steel are 17.65 mpy at corrosive media HCl 1M and immersion time 20.69 hours. Corrosion rate test on carbon steel showed that the influential variable was immersion time, concentration of corrosive media and inhibitors concentration.Keywords: central composite design, corrosion rate, gigantochloa apus leaves, inhibitors